Hubungan Psikolinguistik dalam Pemerolehan dan Pembelajaran Bahasa - Maria Fatima Tae; Liliana Ximenes; Ofra Talelu; Selestina Niis; Yulita Abuk; Yustina Sako (Institut Nalanda, 2025)
Psycholinguistic Relationships in Language Acquisition and Learning. Through psychology we can learn about students' attitudes and behavior in acquiring and learning language, while through linguistics we can learn about language concepts and structures. At the stage of language acquisition, four phases of language acquisition in children were found, namely 1. Babel level (starting from age 0-1 year), 2. Holophrase period (starting at age 1-2 years), 3. Sensorimotor stage (starting at age 2 -3 years) 4. Pre-operational stage. (starts at age 3-5 years). Language learning is not only done formally in formal settings, for example language learning in the classroom. However, it is not important to study anywhere, even if it is not in the classroom, as long as the learning process is directed at the conscious mastery of linguistic rules by educators and students, then the process is called learning. In the formal and non-formal learning process, the psycholinguistic process works to obtain language knowledge through learning. So that interdisciplinarity can accompany educators to understand the processes that occur within each student when they try to understand and provide understanding of the material in language learning presented in class.